2005
DOI: 10.4049/jimmunol.175.3.1609
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Location Determines the Distribution and Function of Dendritic Cells and Other APCs in the Respiratory Tract

Abstract: APCs, including dendritic cells (DC), are central to Ag surveillance in the respiratory tract (RT). Research in this area is dominated by mouse studies on purportedly representative RT-APC populations derived from whole-lung digests, comprising mainly parenchymal tissue. Our recent rat studies identified major functional differences between DC populations from airway mucosal vs parenchymal tissue, thus seriously questioning the validity of this approach. We addressed this issue for the first time in the mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
240
3
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(251 citation statements)
references
References 46 publications
(37 reference statements)
6
240
3
2
Order By: Relevance
“…S1A, Left). By gating on Alexa 647 + , CD45 + lung cells, we found that, 24 h after delivery, the majority of cells involved in NP uptake (80% of Alexa 647 + cells) were a subset of CD11c + , F4/80 + , CD11b low , MHC-II low , highly autofluorescent macrophages that have previously been shown to reside in the lung parenchyma (19,20). The remaining proportion (20% of Alexa 647 + cells) consisted of CD11c + , MHC-II high DCs (Fig.…”
Section: Nps Delivered To the Lung Are Efficiently Taken Up By Dcs Wimentioning
confidence: 97%
“…S1A, Left). By gating on Alexa 647 + , CD45 + lung cells, we found that, 24 h after delivery, the majority of cells involved in NP uptake (80% of Alexa 647 + cells) were a subset of CD11c + , F4/80 + , CD11b low , MHC-II low , highly autofluorescent macrophages that have previously been shown to reside in the lung parenchyma (19,20). The remaining proportion (20% of Alexa 647 + cells) consisted of CD11c + , MHC-II high DCs (Fig.…”
Section: Nps Delivered To the Lung Are Efficiently Taken Up By Dcs Wimentioning
confidence: 97%
“…We have shown that airway RTDC become activated and up-regulate their capacity to capture and process inhaled allergen prior to the onset of Th2-mediated airways inflammation in mice, suggesting that RTDC play an important early role in the activation and recruitment of Th2 cells to the airways (von Garnier et al, 2007). In addition to the airway epithelium, RTDC subsets are also present in the submucosa and lung parenchyma although subset distribution and turnover rates differ at these sites (Holt et al, 1994;von Garnier et al, 2005). We and others have shown that RTDC are capable of capturing inhaled allergens and rapidly transporting these to DLN for presentation to T cells and that the rate of this transport can be modified by microbial products (Vermaelen et al, 2001(Vermaelen et al, , 2003Wikstrom et al, 2006).…”
Section: Distribution and Function Of Respiratory Tract Dendritic Cellsmentioning
confidence: 99%
“…Two main subsets of murine RTDC have been identified -myeloid DC (Lambrecht et al, 2000a,b) and plasmacytoid DC (de Heer et al, 2004), with further subsets evident dependant on anatomical location (von Garnier et al, 2005).…”
Section: Distribution and Function Of Respiratory Tract Dendritic Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In alveolar space, a population of alveolar MPh is also present. In the RT, tracheal DC have a rapid turnover rate (2-3 days), while interstitial DC are long lived (Holt et al 1994;von Garnier et al 2005).…”
Section: The Phagocyte System Of the Rtmentioning
confidence: 99%